Positive electrode material, preparation method thereof, positive electrode plate and lithium ion battery

By designing the three-layer structure of the core, transition layer and cladding layer in the lithium cobalt oxide positive electrode material, using the doping technology of M, A, G and D elements, the lithium cobalt oxide positive electrode material is solved at high voltage and high temperature. Stability issues achieve the effect of high capacity and long-term stable work.

CN119447233AActive Publication Date: 2025-02-14GUANGDONG BRUNP RECYCLING TECH CO LTD +1

Patent Information

Application Number
CN202411522357.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The lithium cobalt oxide cathode material has problems such as lithium ion self-deintercalation, unstable lattice structure, loss of active element cobalt and electrolyte components under high voltage, resulting in irreversible attenuation of capacity, especially under high temperature conditions.

Method used

The three-layer structure positive electrode material is adopted for core, transition layer and cladding layer. The core is lithium cobalt oxide doped with M element. The transition layer contains gradient doping of elements A and G elements. The cladding layer is an oxide of element D. This structure synergistically works to improve the electrochemical cycling performance and high-voltage stability of the material.

Benefits of technology

It realizes a long-term stable operation while maintaining high capacity at high voltage (4.55V), improving the high temperature and high pressure stability and electrochemical cycling performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447233A_ABST
    Figure CN119447233A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery materials, and provides a positive electrode material, a preparation method thereof, a positive electrode plate and a lithium ion battery. The positive electrode material comprises an inner core, a transition layer and a coating layer. The inner core comprises lithium cobalt oxide doped with an element M, the transition layer comprises lithium cobalt oxide doped with an element A, an element G and the element M, and the coating layer comprises an oxide of an element D. The preparation method of the positive electrode material comprises the following steps: mixing and sintering a cobalt source, a lithium source and an M element source to obtain a lithium cobalt oxide matrix; treating the lithium cobalt oxide matrix in an ammonium salt solution, and sintering to obtain a first pretreated lithium cobalt oxide matrix; placing the first pretreated lithium cobalt oxide matrix in a solution containing an element A and an element G, and performing stirring treatment to obtain a second pretreated lithium cobalt oxide matrix; and mixing the second pretreated lithium cobalt oxide matrix with a D element source, and sintering to obtain the positive electrode material. The positive electrode material has high-voltage stability and can stably work for a long time on the premise of keeping high capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion battery materials, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium-ion battery. Background Art

[0002] Lithium cobalt oxide (LiCoO2) has long dominated the consumer battery market due to its high volume energy density, simple production method and excellent reliability. Lithium cobalt oxide positive electrode materials have a large capacity improvement space (theoretical specific capacity is as high as 274mAh / g), and a higher discharge specific capacity can be obtained by increasing the cut-off voltage. However, at high voltage (such as 4.5V), the degree of lithium ion self-deintercalation of lithium cobalt oxide is high, resulting in an unstable layered structure of lithium cobalt oxide, severe deformation of the lattice structure, and easy collapse; the Co in lithium cobalt oxide is 3+ Oxidized to Co 4+ , the formed Co 4+ It has strong oxidizing properties and reacts with the electrolyte, resulting in the loss of active element cobalt and the consumption of components in the electrolyte, causing irreversible attenuation of the capacity of the lithium cobalt oxide battery. Under high temperature conditions, the capacity attenuation of lithium cobalt oxide batteries is more serious. In order to solve the above problems, researchers use element doping of lithium cobalt oxide to improve lattice stability and reduce interface side reactions.

[0003] Gradient doping can not only improve the stability of the material structure, but also reduce the structural mutation caused by the sudden change of the doping element concentration. At present, gradient doping is often prepared by co-precipitation method using salt solution with concentration gradient, which is difficult to control.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. In order to make up for the deficiencies and defects of the prior art, the present invention has conducted research on the positive electrode material of lithium ion batteries, focusing on improving the structure and components of lithium cobalt oxide. The positive electrode material provided by the present invention has a three-layer structure of a core, a transition layer and a coating layer. The synergistic effect of the three-layer structure enables the positive electrode material provided by the present invention to have good electrochemical cycle performance at high voltage (4.55V), and can work stably for a long time while maintaining high capacity.

[0006] The present invention is achieved in that: In a first aspect, the present invention provides a positive electrode material, comprising a core, a transition layer and a coating layer.

[0007] The core includes lithium cobalt oxide doped with an M element, wherein M includes at least one of Ni, Mn, Mg, Al, Zr, La, Y and Ti elements; The transition layer is located on the surface of the core; the transition layer comprises lithium cobalt oxide doped with A element, G element and M element; the A element and the G element are distributed in a gradient in the transition layer; the A element comprises at least one of F, Cl, S, Br, P, Se and N, and the G element comprises at least one of Ni, Co and Mn; The coating layer is located on the surface of the transition layer and includes an oxide of the D element; the D element includes at least one of Ni, Co, Mn, Al, Zr, La, Y, Tb, F, P, Ti, Mg and Li elements.

[0008] In an optional embodiment, the positive electrode material satisfies at least one of the following (1) to (5): (1): The concentrations of the A element and the G element in the transition layer are distributed in an increasing manner in a direction away from the core; (2): The D element includes Co; (3): The thickness of the transition layer is 0.1 nm to 50 nm; (4): The coating layer has a thickness of 0.1 nm to 200 nm; (5): The Dv50 of the positive electrode material is 3µm~8µm.

[0009] In a second aspect, the present invention provides a method for preparing the positive electrode material as described in the first aspect, comprising the following steps: S1, mixing a cobalt source, a lithium source and an M element source to obtain a first mixed material; performing a first sintering on the first mixed material to obtain a lithium cobalt oxide matrix; S2, dispersing the lithium cobalt oxide matrix in an ammonium salt solution, performing a first stirring, and performing a second sintering after solid-liquid separation to obtain a first pretreated lithium cobalt oxide matrix; S3, placing the first pretreated lithium cobalt oxide matrix in a solution containing an A element source and a G element source, performing a second stirring, and evaporating the solvent to obtain a second pretreated lithium cobalt oxide matrix; S4, mixing the second pretreated lithium cobalt oxide matrix and the D element source, sintering for the third time, crushing and sieving to obtain the positive electrode material.

[0010] In an optional embodiment, the ammonium salt in the ammonium salt solution includes at least one of ammonium chloride, ammonium fluoride, ammonium sulfate, ammonium nitrate, and ammonium carbonate, and the concentration of the ammonium salt solution is 2 mol / L to 10 mol / L.

[0011] In an optional embodiment, step S1 satisfies at least one of the following (6) to (10): (6): The M element of the M element source includes at least one of Ni, Mn, Mg, Al, Zr, La, Y and Ti; (7): The M element source includes at least one of the hydroxide, oxide, carbonate, nitrate, sulfate, soluble halide and acetate of the M element; (8): The mass of the M element source is 0.03% to 0.2% of the mass of the first mixed material; (9): The molar ratio of cobalt ions in the cobalt source to lithium ions in the lithium source is 1: (1-1.05); (10): The temperature of the first sintering is 800°C~1000°C, and the duration is 5h~10h.

[0012] In an optional embodiment, step S2 satisfies at least one of the following (11) to (12): (11): The first stirring time is 10 h to 48 h; (12): The temperature of the second sintering is 400°C~800°C, and the duration is 3h~6h.

[0013] In an optional embodiment, step S3 satisfies at least one of the following (13) to (15): (13): The A element of the A element source includes at least one of F, Cl, S, Br, P, Se and N, and the G element of the G element source includes at least one of Ni, Co and Mn; (14): The total mass of the A element source and the G element source is 0.5% to 1.5% of the mass of the first pretreated lithium cobalt oxide matrix, and the molar ratio of A in the A element source to G in the G element source is 0.3-1:1; (15): The temperature of the second stirring is 100°C~150°C.

[0014] In an optional embodiment, step S4 satisfies at least one of the following (16) to (18): (16): The D element of the D element source includes at least one of Ni, Co, Mn, Al, Zr, La, Y, Tb, F, P, Ti, Mg and Li; (17): The mass of the D element source is 0.3% to 2.5% of the mass of the second pretreated lithium cobalt oxide matrix; (18): The temperature of the third sintering is 500°C~900°C, and the duration is 5h~10h.

[0015] In a third aspect, the present invention provides a positive electrode plate, which includes the positive electrode material provided in the first aspect or the positive electrode material prepared by the preparation method provided in the second aspect.

[0016] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet provided in the third aspect.

[0017] The present invention has the following beneficial effects: (1) The positive electrode material provided by the present invention has a three-layer structure of a core, a transition layer and a coating layer. The core includes lithium cobalt oxide doped with a metal element M in the bulk phase. The element doping at the bulk phase level can expand the lattice spacing and improve the Li + The diffusion rate of the cathode material is increased by 20%. The transition layer includes anions of element A and cations of element G. The co-doping of anions and cations can stabilize the crystal lattice structure and reduce the precipitation of oxygen on the crystal surface. The two ions are distributed in a gradient in the transition layer, which improves the stability of the material structure and reduces the structural mutation caused by the sudden change of the concentration of the doped elements. The coating layer is an oxide including element D, which can reduce the contact between the active material in the cathode material and the electrolyte. The above three-layer structure works synergistically, so that the cathode material obtained not only has a good discharge specific capacity, but also has high-voltage stability, and can work stably for a long time while maintaining high capacity.

[0018] (2) The present invention uses ammonium ions in an ammonium salt solution to replace lithium ions in lithium cobalt oxide, and then removes the ammonium ions by sintering to obtain lithium cobalt oxide with gradient lattice vacancies on the surface, so as to facilitate the subsequent anion-cation gradient co-doping. The method is simple to operate, and the ammonium salt solution spontaneously diffuses from the surface of the lithium cobalt oxide to the interior of the lithium cobalt oxide, so that the amount of replaced lithium ions is distributed in a decreasing gradient from the surface to the inside, and the gradient distribution is relatively uniform and easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 This is a scanning electron microscope image of the positive electrode material prepared in Example 1; Figure 2 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.

[0022] In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0023] For simplicity, the present invention specifically discloses some numerical ranges, and various numerical ranges can be combined with each other to form corresponding embodiments. The endpoints and any value of the scope disclosed in the present disclosure are not limited to this accurate scope or value, and these scopes or values ​​should be understood as comprising values ​​close to these scopes or values. For numerical range, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between the separate point value, can be combined with each other and obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.

[0024] Unless otherwise specified, the terms used in the present invention have the commonly understood meanings that are generally understood by those skilled in the art.

[0025] The following is a detailed description of a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium-ion battery provided by the present invention.

[0026] At present, the high-voltage stability of lithium cobalt oxide positive electrode materials is poor; high capacity can be obtained under high voltage, but it cannot work stably for a long time and has poor cycle performance. In order to solve the above technical problems, the present invention proposes the following technical solutions.

[0027] The invention provides a positive electrode material, which comprises a core, a transition layer and a coating layer.

[0028] The core includes lithium cobalt oxide doped with an M element, wherein M includes at least one of Ni, Mn, Mg, Al, Zr, La, Y and Ti. The lithium cobalt oxide doped with the metal element M in the bulk phase can expand the lattice spacing at the bulk phase level and improve the Li + The diffusion rate.

[0029] The transition layer is located on the surface of the core; the transition layer includes lithium cobalt oxide doped with A element, G element and M element; the A element and the G element are distributed in a gradient in the transition layer; the A element includes at least one of F, Cl, S, Br, P, Se and N, and the G element includes at least one of Ni, Co and Mn. The ions containing the A element are anions, and the ions containing the G element are cations. The co-doping of anions and cations can stabilize the crystal lattice structure and reduce the precipitation of oxygen on the crystal surface.

[0030] The coating layer is located on the surface of the transition layer and includes an oxide of the D element; the D element includes at least one of Ni, Co, Mn, Al, Zr, La, Y, Tb, F, P, Ti, Mg and Li. The coating layer can reduce the contact between the active material in the positive electrode material and the electrolyte, and reduce the generation of interface side reactions.

[0031] The above three-layer structure works synergistically, so that the obtained positive electrode material not only has a good discharge specific capacity, but also has high-voltage stability, and can work stably for a long time while maintaining high capacity.

[0032] In some embodiments, the concentrations of element A and element G in the transition layer are distributed in an increasing manner along the direction away from the core, that is, the closer to the surface of the material particles, the more element A and element G are doped, which can stabilize the lattice structure of the crystal surface and reduce the precipitation of oxygen on the crystal surface.

[0033] In some embodiments, the D element includes Co. The oxide of the Co element has high electrical conductivity and Li + The diffusion rate will not significantly affect the Li + The deintercalation speed can stabilize the surface structure of the positive electrode material as a coating layer.

[0034] In some embodiments, the transition layer has a thickness of 0.1 nm to 50 nm.

[0035] In some embodiments, the coating layer has a thickness of 0.1 nm to 200 nm.

[0036] In some embodiments, the Dv50 of the positive electrode material is 3µm~8µm.

[0037] Accordingly, the present invention provides a method for preparing a positive electrode material, comprising the following steps: S1. Mix a cobalt source, a lithium source and an M element source to obtain a first mixed material; and perform a first sintering on the first mixed material to obtain a lithium cobalt oxide matrix.

[0038] In some embodiments, the particle size Dv50 of the cobalt source is 3µm to 5µm, which is beneficial to improving the discharge specific capacity of the positive electrode material within this range.

[0039] In some embodiments, the M element of the M element source includes at least one of Ni, Mn, Mg, Al, Zr, La, Y and Ti. The doping of M element can increase the c-axis spacing of the lithium cobalt oxide crystal and improve the Li + The diffusion rate of lithium cobalt oxide can be reduced, while suppressing the phase transition of the layered structure of lithium cobalt oxide crystals during the cycling process.

[0040] In some embodiments, the source of element M includes at least one of a hydroxide, an oxide, a carbonate, a nitrate, a sulfate, a soluble halide, and an acetate of element M.

[0041] In some embodiments, the mass of the M element source is 0.03% to 0.2% of the mass of the first mixed material.

[0042] In some embodiments, the molar ratio of cobalt ions in the cobalt source to lithium ions in the lithium source is 1:(1-1.05).

[0043] In some embodiments, the first sintering is performed at a temperature of 800° C. to 1000° C. for a duration of 5 h to 10 h.

[0044] S2, dispersing the lithium cobalt oxide matrix in an ammonium salt solution, performing a first stirring, and performing a second sintering after solid-liquid separation to obtain a first pretreated lithium cobalt oxide matrix.

[0045] In some embodiments, after the solid-liquid separation, the solid product obtained by the solid-liquid separation is further washed with deionized water, dried, and ground, and then subjected to a second sintering after grinding.

[0046] The lithium cobalt oxide matrix is ​​dispersed in an ammonium salt solution. The ammonium ions in the ammonium salt solution can replace the lithium ions in the lithium cobalt oxide matrix to obtain an ammonium ion-doped lithium cobalt oxide matrix; after the ammonium ions are removed by a second sintering, O vacancies and Li vacancies are left on the surface of the first pretreated lithium cobalt oxide matrix to facilitate subsequent doping. Because the ammonium salt solution diffuses from the surface of the lithium cobalt oxide matrix to the inside of the lithium cobalt oxide matrix, the number of vacancies left is distributed in an increasing gradient from the inside to the outside. The amount of vacancies on the surface of the first pretreated lithium cobalt oxide matrix can be controlled by adjusting the concentration of the ammonium salt solution or the first stirring time.

[0047] In some embodiments, the ammonium salt in the ammonium salt solution includes at least one of ammonium chloride, ammonium fluoride, ammonium sulfate, ammonium nitrate, and ammonium carbonate; the concentration of the ammonium salt solution is 2 mol / L to 10 mol / L, for example, it can be any one of 2 mol / L, 5 mol / L, 7 mol / L, 10 mol / L or a range value between any two of them.

[0048] In some embodiments, the duration of the first stirring is 10 h to 48 h, for example, it can be any one of 10 h, 15 h, 24 h, 30 h, 48 h, or a range value between any two of them.

[0049] In some embodiments, the drying temperature is 80° C. and the drying time is 24 h.

[0050] In some embodiments, the temperature of the second sintering is 400°C~800°C, for example, it can be any one of 400°C, 500°C, 600°C, 700°C, 800°C or a range between any two of them; the duration of the second sintering is 3h~6h, for example, it can be any one of 3h, 4h, 5h, 6h or a range between any two of them.

[0051] S3, placing the first pretreated lithium cobalt oxide substrate in a solution containing an A element source and a G element source, performing a second stirring, and evaporating the solvent to obtain a second pretreated lithium cobalt oxide substrate.

[0052] In some embodiments, the evaporation of the solvent further includes drying.

[0053] In some embodiments, the A element of the A element source includes at least one of F, Cl, S, Br, P, Se and N, and the ions containing the A element are anions or polyanions, which are doped into the vacancies of the first pretreated lithium cobalt oxide matrix. The G element of the G element source includes at least one of Ni, Co and Mn, and the ions containing the G element are cations, which are doped into the vacancies of the first pretreated lithium cobalt oxide matrix.

[0054] Since different radii and diffusion coefficients affect the diffusion of ions in lithium cobalt oxide crystals, gradient doping can be achieved by doping different ions. Due to their low diffusion coefficient, ions containing element A can only stay on the surface lattice, stabilizing the oxygen on the surface lattice and reducing oxygen precipitation, which helps to inhibit the formation of Co 4+ Interaction with the electrolyte. The radius of the ion containing the G element and Li + Therefore, the ions containing the G element occupy the lithium vacancies of the first pretreated lithium cobalt oxide matrix by diffusion, preventing the lattice drastic change of the layered structure of the positive electrode material under the high lithium removal state and improving the lattice stability. In summary, the simultaneous doping of anions containing the A element and cations containing the G element can improve the high-voltage stability of the positive electrode material.

[0055] In S2, the amount of vacancies on the surface of the first pretreated lithium cobalt oxide matrix is ​​distributed in a decreasing gradient from the outside to the inside; in S3, gradient doping can be achieved by doping ions with different radii and diffusion coefficients. Therefore, the combination of S2 and S3 can achieve excellent anion and cation gradient doping containing A and G elements on the surface of the positive electrode material to prepare the second pretreated lithium cobalt oxide matrix.

[0056] In some embodiments, the total mass of the A element source and the G element source is 0.5% to 1.5% of the mass of the first pretreated lithium cobalt oxide matrix, and the molar ratio of A in the A element source to G in the G element source is 0.3-1:1.

[0057] In some embodiments, the second stirring temperature is 100°C to 150°C.

[0058] In some embodiments, the rotation speed of the second stirring is 500 rpm to 800 rpm, and the rotation speeds of the first stirring and the second stirring may be the same or different.

[0059] S4, mixing the second pretreated lithium cobalt oxide matrix and the D element source, sintering for the third time, crushing and sieving to obtain a positive electrode material.

[0060] It should be noted that the D element source generates the D element oxide after the third sintering reaction. The D element oxide is the coating layer, which can prevent the active material in the positive electrode material from directly contacting the electrolyte, reduce Co dissolution, and inhibit oxygen precipitation.

[0061] In some embodiments, the D element of the D element source includes at least one of Ni, Co, Mn, Al, Zr, La, Y, Tb, F, P, Ti, Mg and Li. The oxide of Co element has high electrical conductivity and Li + The diffusion rate will not significantly affect the Li + De-embedding speed.

[0062] In some embodiments, the mass of the D element source is 0.3% to 2.5% of the mass of the second pretreated lithium cobalt oxide matrix.

[0063] In some embodiments, the third sintering is performed at a temperature of 500° C. to 900° C. for a duration of 5 h to 10 h.

[0064] The features and performances of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.

[0065] Example 1 This embodiment provides a positive electrode material, and the preparation method thereof includes: S1. 7 kg Co3O4, 3.3 kg Li2CO3, 8 g Mg(OH)2 and 6 g Al2O3 were mixed evenly to obtain a first mixed material. The first mixed material was sintered at 1000° C. for 10 h, and then crushed and sieved to obtain a lithium cobalt oxide matrix.

[0066] S2, dispersing the lithium cobalt oxide matrix in a 5 mol / L NH4Cl aqueous solution for a first stirring, and obtaining a solid product after solid-liquid separation. The solid product is washed with deionized water, dried at 80° C. for 24 h, ground, and sintered at 500° C. for 6 h to obtain a first pretreated lithium cobalt oxide matrix.

[0067] The duration of the first stirring is 24 hours, and the rotation speed of the first stirring is 500 rpm.

[0068] S3. Place the first pretreated lithium cobalt oxide substrate in an anhydrous ethanol solution containing H3PO4 and Ni(CH3COO)2 (solid-to-liquid ratio of 1g:2g), stir for a second time, evaporate the solvent, and then dry at 120°C to obtain a second pretreated lithium cobalt oxide substrate.

[0069] Among them, the total mass of H3PO4 and Ni(CH3COO)2 is 0.75% of the mass of the first pretreated lithium cobalt oxide matrix; the molar ratio of P element to Ni element is 0.3:1; the temperature of the second stirring is 110°C, and the speed of the second stirring is 600rpm.

[0070] S4, take 80g of the second pretreated lithium cobalt oxide matrix, 0.63g Co(OH)2, 0.25g MnO2, 0.21g Y2O3 and 0.12g AlOOH, mix them, sinter them at 500℃ for 5h, crush and sieve them to obtain the positive electrode material.

[0071] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 30nm-40nm, and the thickness of the coating layer is 100nm-150nm.

[0072] Instructions attached Figure 1 This is a scanning electron microscope image of the positive electrode material obtained in this example. It can be seen from the image that the positive electrode material particles are about 5 μm, have good dispersion and no obvious agglomeration, and the surface of the positive electrode material particles is rough as a coating layer.

[0073] Example 2 This embodiment provides a positive electrode material, and the preparation method thereof includes: S1. 7 kg Co3O4, 3.3 kg Li2CO3, 3 g Mg(OH)2 and 2 g Al2O3 were mixed evenly to obtain a first mixed material. The first mixed material was sintered at 1000° C. for 5 h, and then crushed and sieved to obtain a lithium cobalt oxide matrix.

[0074] S2, dispersing the lithium cobalt oxide matrix in a 2 mol / L NH4F aqueous solution for a first stirring, and obtaining a solid product after solid-liquid separation. The solid product is washed with deionized water, dried at 80° C. for 24 h, ground, and sintered at 800° C. for 3 h to obtain a first pretreated lithium cobalt oxide matrix.

[0075] The duration of the first stirring was 48 h, and the rotation speed of the first stirring was 500 rpm.

[0076] S3. Place the first pretreated lithium cobalt oxide substrate in an anhydrous ethanol solution containing H3PO4 and Ni(CH3COO)2 (solid-to-liquid ratio of 1g:2g), stir for a second time, evaporate the solvent, and then dry at 120°C to obtain a second pretreated lithium cobalt oxide substrate.

[0077] Among them, the total mass of H3PO4 and Ni(CH3COO)2 is 0.9% of the mass of the first pretreated lithium cobalt oxide matrix; the molar ratio of P element to Ni element is 0.4:1; the temperature of the second stirring is 100°C, and the speed of the second stirring is 600rpm.

[0078] S4, take 80g of the second pretreated lithium cobalt oxide matrix, 0.25g Co(OH)2, 0.04g MnO2, 0.03g Y2O3 and 0.09g AlOOH, mix them, sinter them at 900℃ for 5h, crush and sieve them to obtain the positive electrode material.

[0079] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 25nm-40nm, and the thickness of the coating layer is 5nm-50nm.

[0080] Example 3 This embodiment provides a positive electrode material, and the preparation method thereof includes: S1. 7 kg Co3O4, 3.3 kg Li2CO3, 13 g Mg(OH)2 and 7.1 g TiO2 were mixed evenly to obtain a first mixed material. The first mixed material was sintered at 800° C. for 10 h, and then crushed and sieved to obtain a lithium cobalt oxide matrix.

[0081] S2, dispersing the lithium cobalt oxide matrix in a 10 mol / L NH4Cl aqueous solution for a first stirring, and obtaining a solid product after solid-liquid separation. The solid product is washed with deionized water, dried at 80° C. for 24 h, ground, and sintered at 400° C. for 6 h to obtain a first pretreated lithium cobalt oxide matrix.

[0082] The duration of the first stirring was 15 h, and the rotation speed of the first stirring was 500 rpm.

[0083] S3. Place the first pretreated lithium cobalt oxide substrate in an anhydrous ethanol solution containing H3PO4 and Ni(CH3COO)2 (solid-to-liquid ratio of 1g:2g), stir for a second time, evaporate the solvent, and then dry at 120°C to obtain a second pretreated lithium cobalt oxide substrate.

[0084] Among them, the total mass of H3PO4 and Ni(CH3COO)2 is 1.5% of the mass of the first pretreated lithium cobalt oxide matrix; the molar ratio of P element to Ni element is 1:1; the temperature of the second stirring is 150°C, and the speed of the second stirring is 800rpm.

[0085] S4, take 80g of the second pretreated lithium cobalt oxide matrix, 0.81g Co(OH)2, 0.25g MnO2, 0.63g CoPO4 and 0.23g AlOOH, mix them, sinter them at 500°C for 10h, crush and sieve them to obtain the positive electrode material.

[0086] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 40nm-50nm, and the thickness of the coating layer is 150nm-200nm.

[0087] Example 4 This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the lithium cobalt oxide matrix is ​​dispersed in a 3 mol / L NH 4 Cl aqueous solution and first stirred in S2 .

[0088] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 25nm-35nm, and the thickness of the coating layer is 100nm-150nm.

[0089] Example 5 This embodiment provides a positive electrode material, which is different from the embodiment 1 only in that the lithium cobalt oxide matrix is ​​dispersed in 8 mol / L NH 4 Cl aqueous solution and first stirred in S2 .

[0090] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 40nm-50nm, and the thickness of the coating layer is 100nm-150nm.

[0091] Example 6 This embodiment provides a positive electrode material, which is different from Embodiment 1 only in that, in S3, the total mass of H3PO4 and Ni(CH3COO)2 is 0.6% of the mass of the first pretreated lithium cobalt oxide matrix.

[0092] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 20nm-35nm, and the thickness of the coating layer is 100nm-150nm.

[0093] Example 7 This embodiment provides a positive electrode material, which differs from Embodiment 1 only in that, in S3, the total mass of H3PO4 and Ni(CH3COO)2 is 1.3% of the mass of the first pretreated lithium cobalt oxide matrix.

[0094] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 40nm-50nm, and the thickness of the coating layer is 100nm-150nm.

[0095] Example 8 This embodiment provides a positive electrode material, which is different from Embodiment 1 only in that, in S3, the molar ratio of the P element to the Ni element is 0.6:1.

[0096] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 25nm-35nm, and the thickness of the coating layer is 100nm-150nm.

[0097] Example 9 This embodiment provides a positive electrode material, which is different from Embodiment 1 only in that the molar ratio of the P element to the Ni element is 0.8:1.

[0098] In the positive electrode material obtained in this embodiment, the thickness of the transition layer is 20nm-30nm, and the thickness of the coating layer is 100nm-150nm.

[0099] Comparative Example 1 This comparative example provides a positive electrode material, which differs from Example 1 in that only step S1 is included (ie, no subsequent treatment is performed on the lithium cobalt oxide substrate).

[0100] Instructions attached Figure 2 This is a scanning electron microscope image of the positive electrode material obtained in this comparative example 1. It can be seen from the image that the surface of the positive electrode material is smooth with a small amount of agglomeration.

[0101] Comparative Example 2 This comparative example provides a positive electrode material, and the preparation method thereof comprises: S1. 7 kg Co3O4, 3.3 kg Li2CO3, 8 g Mg(OH)2 and 6 g Al2O3 were mixed evenly to obtain a first mixed material. The first mixed material was sintered at 1000° C. for 10 h, and then crushed and sieved to obtain a lithium cobalt oxide matrix.

[0102] S2, dispersing the lithium cobalt oxide matrix in a 5 mol / L NH4Cl aqueous solution for a first stirring, and obtaining a solid product after solid-liquid separation. The solid product is washed with deionized water, dried at 80° C. for 24 h, ground, and sintered at 500° C. for 6 h to obtain a first pretreated lithium cobalt oxide matrix.

[0103] The duration of the first stirring is 24 hours, and the rotation speed of the first stirring is 500 rpm.

[0104] S3, placing the first pretreated lithium cobalt oxide matrix in an anhydrous ethanol solution containing H3PO4 and Ni(CH3COO)2 (solid-liquid ratio of 1g:2g), stirring for a second time, evaporating the solvent, and drying at 120°C to obtain a second pretreated lithium cobalt oxide matrix. The second pretreated lithium cobalt oxide matrix was directly sintered at 500°C for 5h, crushed, and sieved to obtain the positive electrode material of this comparative example 2.

[0105] Among them, the total mass of H3PO4 and Ni(CH3COO)2 is 0.75% of the mass of the first pretreated lithium cobalt oxide matrix; the molar ratio of P element to Ni element is 0.3:1; the temperature of the second stirring is 110°C, and the speed of the second stirring is 600rpm.

[0106] Comparative Example 3 This comparative example provides a positive electrode material, and the preparation method thereof comprises: 7kg Co3O4, 3.3kg Li2CO3, 8g Mg(OH)2 and 6g Al2O3 were mixed evenly to obtain a first mixed material. The first mixed material was sintered at 1000°C for 10 hours, and then crushed and sieved to obtain a lithium cobalt oxide matrix.

[0107] 80 g of lithium cobalt oxide matrix, 0.63 g of Co(OH)2, 0.25 g of MnO2, 0.21 g of Y2O3 and 0.12 g of AlOOH were mixed, sintered at 500°C for 5 h, crushed and sieved to obtain the positive electrode material of Comparative Example 3.

[0108] Comparative Example 4 This comparative example provides a positive electrode material, and the preparation method thereof comprises: 7kg Co3O4, 3.3kg Li2CO3, 8g Mg(OH)2 and 6g Al2O3 were mixed evenly to obtain a first mixed material. The first mixed material was sintered at 1000°C for 10 hours, and then crushed and sieved to obtain a lithium cobalt oxide matrix.

[0109] Take 80g of lithium cobalt oxide matrix, 0.51g Ni(CH3COO)2, 0.09g H3PO4, 0.63g Co(OH)2, 0.25g MnO2, 0.21g Y2O3 and 0.12g AlOOH, mix them, sinter them at 500℃ for 5h, crush and sieve them to obtain the positive electrode material of this comparative example 4.

[0110] Test Example 1 The size and distribution of the positive electrode material particles were tested using a laser particle size analyzer. The particle size test results were expressed as median particle size Dv50. The test results are shown in Table 1.

[0111] Test Example 2 The positive electrode material obtained above, the conductive agent Super P and PVDF are uniformly coated on aluminum foil in a ratio of 92:4:4, and pressed to obtain a positive electrode sheet. The positive electrode sheet, the graphite negative electrode sheet, the electrolyte and the separator are assembled into a battery.

[0112] The discharge specific capacity of each battery was tested at a current density of 0.1C in the range of 3V~4.55V.

[0113] After charging and discharging activation, each battery was stored in a 60°C oven, and the battery was charged and discharged at 0.1C every 2 days, and the capacity retention rate of the battery after 10 days was calculated. The test results are shown in Table 1.

[0114] Table 1

[0115] From Table 1, it can be seen from the comparison between Examples 1-9 and Comparative Examples 1-4 that under the high temperature storage environment of 60°C and the high voltage charge and discharge condition of 4.55V, the positive electrode material prepared by the present invention has excellent electrical properties, and its battery capacity retention rate can reach 70.3%, while the battery capacity retention rate of Comparative Example 1 is only 5.2%. When the positive electrode material does not have the above-mentioned transition layer or coating layer, its battery capacity retention rate cannot achieve good performance, which proves that the simultaneous presence of the transition layer and the coating layer can give the positive electrode material better high temperature and high pressure stability.

[0116] Comparative Example 4 uses the same quality of raw materials as Example 1 to modify the lithium cobalt oxide matrix. Due to the different modification methods, Comparative Example 4 has a better discharge specific capacity, but the capacity retention rate is low. Comparative Example 4 does not perform liquid phase treatment on the lithium cobalt oxide matrix, resulting in the presence of common residual lithium on the surface of the lithium cobalt oxide matrix. Direct coating of the lithium cobalt oxide matrix can absorb this part of the residual lithium and generate compounds that are conducive to lithium ion insertion and extraction, resulting in a high discharge specific capacity. Comparing the data of Example 1 and Comparative Example 4, it is proved that only a coating layer without an anion- and cation-doped transition layer is not enough to improve the high temperature and high pressure stability of the positive electrode material.

[0117] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode material, characterized in that: It includes a core, a transition layer and a cladding layer; The core includes lithium cobalt oxide doped with an M element, wherein M includes at least one of Ni, Mn, Mg, Al, Zr, La, Y and Ti elements; The transition layer is located on the surface of the core; the transition layer comprises lithium cobalt oxide doped with A element, G element and M element; the A element and the G element are distributed in a gradient in the transition layer; the A element comprises at least one of F, Cl, S, Br, P, Se and N, and the G element comprises at least one of Ni, Co and Mn; The coating layer is located on the surface of the transition layer and includes an oxide of the D element; the D element includes at least one of Ni, Co, Mn, Al, Zr, La, Y, Tb, F, P, Ti, Mg and Li elements.

2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following (1) to (5): (1): The concentrations of the A element and the G element in the transition layer are distributed in an increasing manner in a direction away from the core; (2): The D element includes Co; (3): The thickness of the transition layer is 0.1 nm to 50 nm; (4): The coating layer has a thickness of 0.1 nm to 200 nm; (5): The Dv50 of the positive electrode material is 3µm~8µm.

3. A method for preparing the positive electrode material according to any one of claims 1 to 2, characterized in that: The steps include: S1, mixing a cobalt source, a lithium source and an M element source to obtain a first mixed material; performing a first sintering on the first mixed material to obtain a lithium cobalt oxide matrix; S2, dispersing the lithium cobalt oxide matrix in an ammonium salt solution, performing a first stirring, and performing a second sintering after solid-liquid separation to obtain a first pretreated lithium cobalt oxide matrix; S3, placing the first pretreated lithium cobalt oxide matrix in a solution containing an A element source and a G element source, performing a second stirring, and evaporating the solvent to obtain a second pretreated lithium cobalt oxide matrix; S4, mixing the second pretreated lithium cobalt oxide matrix and the D element source, sintering for the third time, crushing and sieving to obtain the positive electrode material.

4. The method for preparing the positive electrode material according to claim 3, characterized in that: The ammonium salt in the ammonium salt solution includes at least one of ammonium chloride, ammonium fluoride, ammonium sulfate, ammonium nitrate, and ammonium carbonate, and the concentration of the ammonium salt solution is 2 mol / L to 10 mol / L.

5. The method for preparing the positive electrode material according to claim 3, characterized in that: Step S1 satisfies at least one of the following (6) to (10): (6): The M element of the M element source includes at least one of Ni, Mn, Mg, Al, Zr, La, Y and Ti; (7): The M element source includes at least one of the hydroxide, oxide, carbonate, nitrate, sulfate, soluble halide and acetate of the M element; (8): The mass of the M element source is 0.03% to 0.2% of the mass of the first mixed material; (9): The molar ratio of cobalt ions in the cobalt source to lithium ions in the lithium source is 1: (1-1.05); (10): The temperature of the first sintering is 800°C~1000°C, and the duration is 5h~10h.

6. The method for preparing the positive electrode material according to any one of claims 3 or 4, characterized in that: Step S2 satisfies at least one of the following (11) to (12): (11): The first stirring time is 10 h to 48 h; (12): The temperature of the second sintering is 400°C~800°C, and the duration is 3h~6h.

7. The method for preparing the positive electrode material according to claim 3, characterized in that: Step S3 satisfies at least one of the following (13) to (15): (13): The A element of the A element source includes at least one of F, Cl, S, Br, P, Se and N, and the G element of the G element source includes at least one of Ni, Co and Mn; (14): The total mass of the A element source and the G element source is 0.5% to 1.5% of the mass of the first pretreated lithium cobalt oxide matrix, and the molar ratio of A in the A element source to G in the G element source is 0.3-1:1; (15): The temperature of the second stirring is 100°C~150°C.

8. The method for preparing the positive electrode material according to claim 3, characterized in that: Step S4 satisfies at least one of the following (16) to (18): (16): The D element of the D element source includes at least one of Ni, Co, Mn, Al, Zr, La, Y, Tb, F, P, Ti, Mg and Li; (17): The mass of the D element source is 0.3% to 2.5% of the mass of the second pretreated lithium cobalt oxide matrix; (18): The temperature of the third sintering is 500°C~900°C, and the duration is 5h~10h.

9. A positive electrode sheet, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 2 or the positive electrode material prepared by the preparation method according to any one of claims 3 to 8.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Lithium cobalt oxide positive electrode material of lithium ion battery with voltage of 4.45 V or above and preparation method of lithium cobalt oxide positive electrode material

    CN111081987A

  • Lithium cobalt oxide positive electrode material and preparation method and application thereof

    CN115642235A

  • Multi-doped composite coated lithium cobalt oxide positive electrode material as well as preparation method and application thereof

    CN116314669A

  • Lithium nickel cobalt manganese oxide positive electrode material, preparation method thereof and lithium ion battery

    CN117790721A

  • Preparation process and application of high-voltage lithium cobalt oxide positive electrode material

    CN118156464A

Cited By

  • High-voltage lithium cobalt oxide positive electrode material and preparation method thereof

    CN121192139A